What Factors Are Slowing Development In the Bangladesh Farming Sector? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Ashan Uddin Ahmed from Centre for Global Change, Bangladesh. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya